PENGARUH APLIKASI KOMPOS JERAMI PADI+PANGKASAN TITHONIA DAN BIOCHAR SEKAM PADI TERHADAP SERAPAN NITROGEN, FOSFOR, DAN KALIUM SERTA PRODUKSI PADI METODE SRI (SYSTEM OF RICE INTENSIFICATION) DI KOTA PADANG - Erick Yuhardi; G Gusnidar; Syafrimen Yasin (Jurnal Tanah dan Sumberdaya Lahan, 2021)
A study that was aimed to examine the effect of rice straw + tithonia pruning compost and rice husk biochar application on N, P and K uptake and rice production of SRI (System of Rice Intensification) method, was carried out from November 2019 - February 2020 in Kuranji District, Padang City, West Sumatra. This study used a randomized block design consisting of 6 treatments and 3 replications. The treatments were A = control, B = 100% K (compost), C = 75% K + 25% B (biochar), D = 50% K + 50% B, E = 25% K + 75% B, and F = 100% B. The results showed that there was an increase of N, P and K uptake by rice with the application of 25% compost + 75% biochar. The treatment increased plant height, total tiller number and grain weight by 30 cm, 25.34 stems and 5.47 t ha-1, respectively higher than that in control.